Trypanosoma cruzi: Evaluation of (-)-cubebin derivatives activity in the messenger RNAs processing - Silva, Márcio Luís Andrade e; Cicarelli, Regina Maria Barretto [UNESP]; Pauletti, Patrícia M.; Luz, Priscilla Paiva; Rezende, Karen Cristina Souza; Januário, Ana Helena; Silva, Rosangela da; Pereira, Ana Carolina; Bastos, Jairo Kenupp; Albuquerque, Sérgio de; Magalhães, Lizandra Guidi; Cunha, Wilson Roberto (Springer Nature, 2011)
No fully effective treatment has been developed since the discovery of Chagas' disease. Since drug-resistant Trypanosoma cruzi strains are occurring and the current therapy is effective in the acute phase but with various adverse side effects, more studies are needed to characterize the susceptibility of T. cruzi to new drugs. Pre-mRNA maturation in trypanosomatids occurs through a process called trans-splicing, which is unusual RNA processing reaction, and it implies the processing of polycistronic transcription units into individual mRNAs; a short transcript spliced leader (SL RNA) is trans-spliced to the acceptor pre-mRNA, giving origin to the mature mRNA. Cubebin derivatives seem to provide treatments with less collateral effects than benznidazole and showed similar or better trypanocidal activities than benznidazole. Therefore, the cubebin derivatives ((-)-6,6′-dinitrohinokinin (DNH) and (-)-hinokinin (HQ)) interference in the mRNA processing was evaluated using T. cruzi permeable cells (Y and BOL (Bolivia) strains) following by RNase protection reaction. These substances seem to intervene in any step of the RNA transcription, promoting alterations in the RNA synthesis, even though the RNA processing mechanism still occurs. Furthermore, HQ presented better activity against the parasites than DNH, meaning that BOL strain seems to be more resistant than Y. © 2011 Springer-Verlag.
Keywords: 6,6' dinitrohinokinin; benznidazole; cubebin derivative; hinokinin; messenger RNA; Piper cubeba extract; plant extract; ribonuclease; unclassified drug; animal cell; antibiotic resistance; antiprotozoal activity; controlled study; drug structure; nonhuman; piper cubeba; Piperaceae; priority journal; ribonuclease protection assay; RNA processing; RNA synthesis; RNA transcription; strain difference; Trypanosoma cruzi; Antiprotozoal Agents; Lignans; RNA, Messenger; Trans-Splicing; Trypanosomatidae